IMPACT OF SMOKING AND SMOKELESS TOBACCO ON ORAL CAVITY (Journal of Pharmaceutical Negative Results, 2022)
Aim: To investigate the effect of Smokeless Tobacco and Smoking on hard and soft tissues of oral cavity.Material and method: We conducted a cross-sectional Study on 150 subjects in regular OPD of Karnavati School of dentistry. A visual oral soft tissue examination and a questionnaire-based Performa were part of the study methodology. The study included individuals who had a history of tobacco use and smoking. Patients were told verbally about the study, and those who agreed to share their personal habits and agreed for an oral examination were chosen as study subjects. A complete history of tobacco consumption and smoking was documented from the patient, including the kind, manner of usage, time span, frequency, and location of the tobacco (if chewable), as well as other harmful habits.Patients with tobacco habits were categorized into three groups based on the inclusion and exclusion criteria, namely as Group A: only Smoking, Group B: only tobacco, Group C: only areca nut Group D: mixed tobacco and areca nut.Result: Dental caries was found in 97(60.2%) and was found more in Group D patients. Gingival recession was found in 86(53.4%) and was found more in group d patients. Smokers’ palate and Smoker’s melanosis was found be associated with group A patients which is 19(61.3%) and 9 (29.9%) respectively. Leukoplakia was found to be more in group A patients which is 99(29.0%). Erythroplakia was found to be more prevalent in group B patients which is 4 (7.4%).Tobacco quid lesion was found to be more prevalent in group D patients which is 20(21%).OSMF was found to be more prevalent in group B patients which is 12 (52.2%). Lichenoid reaction was found to be more prevalent in Group B patients which is 3 (13%).Carcinoma of oral cavity was to be more prevalent in Group D patients which is 10 (10.9%).Conclusion: Smoking and using smokeless tobacco both raise a person's risk of developing oral premalignant lesions and oral cancer. It also has a lot of negative consequences on the teeth and other structures. All medical professionals should evaluate their patients' tobacco use patterns and actively implement programs for tobacco prevention, cessation, and treatment.